1970
DOI: 10.1080/00288233.1970.10430507
|View full text |Cite
|
Sign up to set email alerts
|

Hill country sheep production

Abstract: Factors associated with mortality in 7,727 lambs born to 7,091 twoto five-year-old ewes over the 9 years 1959-67 were studied. The lambs were from two Romney flocks and first-, second-, third-, and fourthcross Border Leicester x Romney flocks. Lamb survival rate (lambs weaned as a percentage of all lambs born) increased with increasing age of dam for both single-and multipleborn lambs. Variation in survival rate between flocks and between female and male lambs was large. In 60% of the dead lambs, 44.6% of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

1974
1974
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(11 citation statements)
references
References 57 publications
1
9
0
1
Order By: Relevance
“…The high preweaning mortality recorded is consistent with estimates of mortality from major sheep producing countries, for example 5 to 25 per cent in New Zealand (Hight and Jury 1970), 22 per cent in Australia (Haughey 1983) and 10 to 35 per cent in the USA (Rook and others 1990). As in most flocks, there were constant attempts to improve lamb survival with the success being limited by the continually changing health status of the flock.…”
Section: Discussionsupporting
confidence: 81%
“…The high preweaning mortality recorded is consistent with estimates of mortality from major sheep producing countries, for example 5 to 25 per cent in New Zealand (Hight and Jury 1970), 22 per cent in Australia (Haughey 1983) and 10 to 35 per cent in the USA (Rook and others 1990). As in most flocks, there were constant attempts to improve lamb survival with the success being limited by the continually changing health status of the flock.…”
Section: Discussionsupporting
confidence: 81%
“…The BR, which had the heaviest live and carcass weights of the breeds in this trial, was shown by Hight & Jury (1969, 1970a to be superior to the straightbred RR in some aspects of production. According to Parker & Wiggins (1969), Pd hoggets grow better than RR, and Pd 2-tooths are also heavier.…”
Section: Discussionmentioning
confidence: 99%
“…Breed differences in lamb mortality due to dystocia have been reported (Hight and Jury 1970), and may, to some extent, be independent of birthweight (Gum 1968). Australian Dorset ewes have a high incidence of dystocia (Fogarty 1971) which is negligible in Border Leicester ewes, although birthweights in both breeds are similar (Fogarty, unpublished data).…”
Section: Introductionmentioning
confidence: 97%
“…High birthweights have been associated with increased dystocia in sheep (Dennis 1970;Hight and Jury 1970) and account for the higher incidence of dystocia in ewes bearing single lambs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation